Learning hukum Izhar and hukum Idgham for Standard 1 student using multimedia approach / Azimah Sairan - Sairan, Azimah (2005)
The Learning Hukum Izhar and Hukum Idgham for Standard 1 Student using Multimedia Approach prototype system is developing through the combination of multimedia elements with interactive 3D element where it uses three-dimensional character animation especially human animation. The interest of developing this application is to bring a new dimension of approach in delivering the information for Learning Hukum Izhar and Hukum Idgham for Standard 1 Student using Multimedia Approach. Normally in the daily lessons, it needs somebody to be a model in showing how to pronounce each of the Hukum Tajwid but in this prototype system, no more human model will be necessary. Instead, the animation and simulation of 3 dimensional models are used. This report discusses the implementation and the findings of Learning Hukum Izhar and Hukum Idgham for Standard 1 Student using Multimedia Approach as a new approach in interactive multimedia. Systematic methods based on multimedia framework have been chosen to implement multimedia relating to this system. In addition, powerful computer systems together with the appropriate multimedia authoring tools are identified in order to fulfill this system prototype requirement. With this Learning Hukum Izhar and Hukum Idgham for Standard 1 Student using Multimedia Approach system, a hope that standard 1 students of Islamic Schools will have an attractive and interesting learning experience of Hukum Tajwid.